2014
DOI: 10.1007/s11356-014-2727-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts from control operations on a recreationally hunted feral swine population at a large military installation in Florida

Abstract: Feral swine were targeted for control at Avon Park Air Force Range in south-central Florida to avert damage to sensitive wetland habitats on the 40,000-ha base. We conducted a 5-year study to assess impacts from control to this population that had been recreationally hunted for many years. Control was initiated in early 2009. The feral swine population was monitored from 2008 to 2012 using a passive tracking index (PTI) during the dry and wet seasons and using recreational hunter take rates from the dry season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The impacts of feral swine population control on damage rates and amounts cannot be appropriately discussed without first reviewing the effects of the control program on the feral swine population levels (see Engeman et al 2014). Using three population metrics, that study found that the feral swine population dropped sharply following the onset of control into 2009 and then remained considerably lower from 2010 to 2012 than in 2008 (pre-control) and in 2009 ).…”
Section: Discussion Population Control and Damagementioning
confidence: 99%
See 2 more Smart Citations
“…The impacts of feral swine population control on damage rates and amounts cannot be appropriately discussed without first reviewing the effects of the control program on the feral swine population levels (see Engeman et al 2014). Using three population metrics, that study found that the feral swine population dropped sharply following the onset of control into 2009 and then remained considerably lower from 2010 to 2012 than in 2008 (pre-control) and in 2009 ).…”
Section: Discussion Population Control and Damagementioning
confidence: 99%
“…Such releases represent an increased opportunity for immigration into the base beyond what might occur naturally among the feral swine living in the vicinity. Previously, Engeman et al (2014) found strong evidence of immigration from that property, implying there might have been artificially increased pressure on the northern plant sites before immigrant swine diffused through the base. Thus, we compared the average proportion of sites with any feral swine damage across years at sites located within 1.6 km of the north border to the average proportion of sites with any feral swine damage located throughout the rest of the base.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanson et al 2009;Lieury et al 2015). One study reported that control efforts were hindered by immigration from a neighbouring hunting reserve where feral pigs were deliberately released (Engeman et al 2014). However, if the AO is too large, it can be impossible to concentrate enough shooting effort to offset in situ reproduction (Simard et al 2013).…”
Section: Other Variablesmentioning
confidence: 99%